Tunable isolated attosecond X-ray pulses with gigawatt peak power from a free-electron laser - Duris, Joseph; Li, Siqi; Driver, Taran; Champenois, Elio G.; Macarthur, James P.; Lutman, Alberto A.; Zhang, Zhen; Rosenberger, Philipp; Aldrich, Jeff W.; Coffee, Ryan; Coslovich, Giacomo; Decker, Franz-Josef; et al. (Nature Photonics, 2020)
The quantum-mechanical motion of electrons in molecules and solids occurs on the sub-femtosecond timescale. Consequently, the study of ultrafast electronic phenomena requires the generation of laser pulses shorter than 1 fs and of sufficient intensity to interact with their target with high probability. Probing these dynamics with atomic-site specificity requires the extension of sub-femtosecond pulses to the soft X-ray spectral region. Here, we report the generation of isolated soft X-ray attosecond pulses with an X-ray free-electron laser. Our source has a pulse energy that is millions of times larger than any other source of isolated attosecond pulses in the soft X-ray spectral region, with a peak power exceeding 100 GW. This unique combination of high intensity, high photon energy and short pulse duration enables the investigation of electron dynamics with X-ray nonlinear spectroscopy and single-particle imaging, unlocking a path towards a new era of attosecond science.
CRIS-Team Scopus Importer:2023-04-20